2020
DOI: 10.3390/ijerph17228559
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics and Risk Factors for Fatality and Severity in Patients with Coronavirus Disease in Korea: A Nationwide Population-Based Retrospective Study Using the Korean Health Insurance Review and Assessment Service (HIRA) Database

Abstract: Background: We aimed to investigate the clinical characteristics and risk factors for fatality and severity in these patients. Methods: In this nationwide population-based retrospective study, we investigated the data of 7339 laboratory-confirmed COVID-19 patients, aged ≥ 18 years, using the Korean Health Insurance Review and Assessment Service (HIRA) database. Comorbidities and medications used were identified using HIRA codes, and severe COVID-19 was defined as that requiring oxygen therapy, mechanical venti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 27 publications
0
36
1
1
Order By: Relevance
“…In studies which reported BMI, we observed higher rates of obesity (BMI�30kg/m 2 ) in patients with severe disease (OR = 1.89, 95% CI: 1.44-2.46; I 2 = 0.0%) [20,21,23,26,30,35]. [26,28,35,38,45] showed no significant differences between patients with severe and non-severe disease.…”
Section: Demographic Characteristicsmentioning
confidence: 54%
“…In studies which reported BMI, we observed higher rates of obesity (BMI�30kg/m 2 ) in patients with severe disease (OR = 1.89, 95% CI: 1.44-2.46; I 2 = 0.0%) [20,21,23,26,30,35]. [26,28,35,38,45] showed no significant differences between patients with severe and non-severe disease.…”
Section: Demographic Characteristicsmentioning
confidence: 54%
“…All studies evaluated data from retrospective patient cohorts, except for four (9.3%) that collected the information prospectively [ 39 , 40 , 56 , 69 ]. Six (14.0%) studies reported population-based data [ 35 , 36 , 42 , 52 , 59 , 62 ], while the others were conducted in a hospital setting. Two (4.7%) studies also included COVID-19 patients based on high clinical or radiological suspicion [ 39 , 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…Most investigators reviewed patient records or used tuberculosis-related diagnostic codes in databases to identify patients having active tuberculosis ( Table 1 ). Fourteen (32.6%) studies reported human immunodeficiency virus (HIV) seroprevalence in their patient cohorts [ 36 , 37 , 42 , 48 50 , 58 – 60 , 62 , 64 , 67 , 69 , 71 ]. Of these, a single study from South Africa provided tuberculosis prevalence and outcome data based on HIV status [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies to date have investigated risk factors associated with the severity of COVID-19. Older patients, male gender, patients had diabetes mellitus, chronic kidney disease, and CVD rate in comorbidities, previous history of pneumonia, dyspnea, headache and neurological symptoms, increase respiratory rates and pulse rate, anemia, malaria infection, neutrophilia, lymphcytopenia, higher glucose levels, HbA1c levels and creatinine levels, increase levels of CRP and d-dimer were associated with increased risks of severe COVID-19 and increase the risk of death from COVID-19 (8)(9)(10). However, little is…”
Section: Introductionmentioning
confidence: 99%